2014
DOI: 10.3168/jds.2013-7266
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen-specific effects on milk yield in repeated clinical mastitis episodes in Holstein dairy cows

Abstract: The objective of this study was to estimate the effects of clinical mastitis (CM) cases due to different pathogens on milk yield in Holstein cows. The first 3 CM cases in a cow's lactation were modeled. Eight categories of pathogens were included: Streptococcus spp.; Staphylococcus aureus; coagulase-negative staphylococci (CNS); Escherichia coli; Klebsiella spp.; cases with CM signs but no bacterial growth (above the level detectable by our microbiological procedures) observed in the culture sample, and cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
83
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(99 citation statements)
references
References 36 publications
11
83
2
3
Order By: Relevance
“…However, in dairy cows the decrease of MY is generally more significant in cows with mastitis. This is particularly true when clinical mastitis occurs (Hertl et al, 2014;Schukken et al, 2009), as in some of the above studies, where good detection performance was reached. In our study, no clinical cases were reported.…”
Section: Detection Characteristics Of Electrical Conductivity With Fumentioning
confidence: 69%
“…However, in dairy cows the decrease of MY is generally more significant in cows with mastitis. This is particularly true when clinical mastitis occurs (Hertl et al, 2014;Schukken et al, 2009), as in some of the above studies, where good detection performance was reached. In our study, no clinical cases were reported.…”
Section: Detection Characteristics Of Electrical Conductivity With Fumentioning
confidence: 69%
“…An IMI caused by CNS, in particular, has been associated with high milk production; some researchers have even suggested that CNS IMI could positively affect milk production (Piepers et al, 2010(Piepers et al, , 2013. However, decreases in milk production due to mastitis is an established phenomenon (Seegers et al, 2003;Hertl et al, 2014;Detilleux et al, 2015). Thus, we may conclude that milk production of cows with IMI would have been even higher in the absence of IMI.…”
Section: Discussionmentioning
confidence: 91%
“…In Belgium and other countries, CM data are not available on a larger scale. Yet, conducting our study on the same herds as a study estimating the IRCM in Flanders (Verbeke et al, 2014) Keane et al, 2013;Oliveira et al, 2013) associated with considerable milk losses worldwide (Hertl et al, 2014), more research on this topic is warranted and justified. Besides (pathogen-specific) IRCM, we also studied SCC at test day.…”
mentioning
confidence: 99%